The pretenses of loyalty: Locke, liberal theory, and American political theology - Perry, John (Oxford University Press, 2011)
Liberalism's turn to loyalty -- Harmonized loyalties & abstract respect : two sides to the tolerationist coin -- Locke's early work : from vizor of religion to veil of ignorance -- A letter concerning toleration : Locke turns to loyalty and beyond -- "All at once in a bundle" : the blurring of the just bounds -- Refusing the turn : Jeffersonian separatists and Lockean natural lawyers -- Locke & loyalty in contemporary political theology : three ways of making the turn